Vergleichende makroskopische Anatomie der Musculi alae und Musculi vertebrales des Mauerseglers (Apus apus, Apodidae, Aves) und der Kolibris (Trochilidae) - Brause, Cristeta (Tierärztliche Hochschule, 2006)
The knowledge about the wing musculature of the common swift (Apus apus) is mostly incomplete and tainted with obsolete anatomical terms. The complete cervical musculature of the common swift has not been described until now. As it is assumed that swifts (Apodi) and the hummingbirds (Trochilidae) are sister-groups, the two skeletal muscle groups, musculi alae and musculi vertebrales, of 8 common swifts (Apus apus) were dissected, described, and presented graphically in the first part of this thesis. The results were compared with those of the investigation on Eulampis jugularis published by ZUSI and BENTZ (1984). In view of the recently postulated sistergroup relationship between Apodiformes and Aegothelidae, a character matrix was established in the second part of this thesis. This matrix was based on morphological data of the wing musculature of Apus apus which is presented in the first part of this thesis. The characteristics of the wing muscles of the hummingbirds and traditional „Caprimulgiformes“ were taken from the literature. A computer-assisted parsimony analysis in NONA (GOLOBOFF 1999) based on this character matrix yielded a bootstrap value of 98% for a taxon including Aegothelidae and Apodiformes. This monophyly hypothesis is supported by eight derived characters. The sistergroup relationship between Apodi and Trochilidae is expressed by a bootstrap value of 73% and was supported by six derived characters. Four of these characters are mentioned here for the first time. In the musculi vertebrales of Apus apus additional anatomical characteristics of the cruciform M. splenius capitis were found. These data supplement earlier descriptions in the literature. Furthermore a varying cruciform deep portion of the M. rectus capitis ventralis is described in detail. In der Literatur sind die Angaben über die Flügelmuskulatur des Mauerseglers (Apus apus) noch größtenteils unvollständig sowie mit einigen Unklarheiten und veralteten Termini behaftet. Die gesamten Musculi vertebrales dieser Art wurden bisher ...